Burden of headache disorders and health care needs assessment among working age population (18–65 years) in rural Haryana, North India - Subham Kansal; Kiran Goswami; Anand Krishnan; Harshal Ramesh Salve; Debashish Chowdhury (Scientific Reports, 2026)
Abstract Headache disorders are among the leading causes of disability worldwide and significantly affect productivity and quality of life. Despite this substantial burden, population-based evidence from rural North India remains limited. This study aimed to estimate burden and assess health care need for headache disorders among adults aged 18–65 years in rural Haryana, North India. A community-based cross-sectional study was conducted in rural area of the Ballabgarh block, Faridabad district. Participants of age 18–65 years were selected through simple random sampling. Interviews were conducted using the validated Headache-Attributed Restriction, Disability, Social Handicap and Impaired Participation (HARDSHIP) questionnaire by house-to-house visit. Headache types were classified using a diagnostic algorithm based on ICHD-3 criteria. Symptom burden was assessed through headache frequency, intensity, and proportion of time spent in the ictal state (pTIS) in last one month. Lost health was estimated using multiplication of pTIS and disability weights. The one-year prevalence of any headache disorder was 53.6% [95% CI: 48.9–58.3]. Tension-type headache was the most common subtype [28.9%, 95% CI: 24.7–33.3], followed by migraine [18.7%, 95% CI: 15.2–22.6], algorithm-defined probable medication-overuse headache (pMOH) [2.8%, 95% CI: 1.5–5.1], and other headaches occurring on more than 15 days per month [2.8%, 95% CI: 1.5–5.1]. Participants with headache spent 3.7% of their time experiencing headache symptoms in the previous month. Lost health was highest for pMOH (5.83%). Nearly one-fifth of participants could benefit from professional health-care intervention. Headache disorders are common among the working-age population and result in health loss and reduced productivity. Strengthening headache management within primary health-care services could help reduce impact of this public health burden.